Pengaruh Jalan Kaki Terhadap Kadar Gula Darah Sewaktu Pada Penderita Diabetes Melitus Tipe 2 di Kelurahan Tuminting Kota Manado - Christiva Maras; Sarwan Sarwan; Cut Mutiya Bunsal (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2023)
Sugar levels that accumulate in the blood due to not being absorbed well by body cells can cause various organ disorders. If not controlled properly, it can lead to various complications that can be life-threatening. Risk factors that can affect blood sugar levels are food, activity, and weight gain. Therefore, one way to keep blood sugar levels under control is by doing walking therapy activities. The purpose of this study was to determine the effect of walking on the fasting blood sugar levels when in patients with type 2 diabetes mellitus in Tuminting Village, Manado City. This research is a quantitative research with a method used pre-experimental method using a with a pre-test-post test one group design approach. The sample was taken based on the number of respondents obtained as many as 19 people using Purposive sampling. Data collection was done by using blood glucose test tools and observation sheets. The results of data analysis using the Paired sample t-test showed P value of 0.001 or smaller than ≤0.05 which means that the alternative hypothesis Ha is accepted or through walking activities can reduce the fasting blood sugar levels when in patients with type 2 diabetes mellitus.